2021
DOI: 10.1038/s41477-021-00908-y
|View full text |Cite|
|
Sign up to set email alerts
|

The reference genome of Miscanthus floridulus illuminates the evolution of Saccharinae

Abstract: Miscanthus, a member of the Saccharinae subtribe that includes sorghum and sugarcane, has been widely studied as a feedstock for cellulosic biofuel production. Here, we report the sequencing and assembly of the Miscanthus floridulus genome by the integration of PacBio sequencing and Hi-C mapping, resulting in a chromosome-scale, high-quality reference genome of the genus Miscanthus. Comparisons among Saccharinae genomes suggest that Sorghum split first from the common ancestor of Saccharum and Miscanthus, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 87 publications
2
28
0
Order By: Relevance
“…However, owing to the complexity of Miscanthus genome, the lack of reliable genome information and unavailable genetic databases limited related research within genus. Recently, chromosome-scale assembly of Miscanthus lutarioriparius genome ( Miao et al, 2020 ), Miscanthus floridulus genome ( Zhang et al, 2021 ), and M. sinensis genome ( Mitros et al, 2020 ) was published, which would provide valuable genetic resource for Miscanthus breeding improvement and molecular regulation network of stress resistance. The NAC gene family is a crucial plant-specific transcription factor family that is well known by its involvement in plant growth and developmental activities along with resistance to biotic and abiotic stresses ( Wang et al, 2014 ; Dalman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the complexity of Miscanthus genome, the lack of reliable genome information and unavailable genetic databases limited related research within genus. Recently, chromosome-scale assembly of Miscanthus lutarioriparius genome ( Miao et al, 2020 ), Miscanthus floridulus genome ( Zhang et al, 2021 ), and M. sinensis genome ( Mitros et al, 2020 ) was published, which would provide valuable genetic resource for Miscanthus breeding improvement and molecular regulation network of stress resistance. The NAC gene family is a crucial plant-specific transcription factor family that is well known by its involvement in plant growth and developmental activities along with resistance to biotic and abiotic stresses ( Wang et al, 2014 ; Dalman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A heterozygosity rate of 0.48% was estimated from the frequency peaks of 17-mers from the Illumina reads following [35], with a main peak depth of 52 [Additional file 1: Fig. S2c (sequence depth), Additional file 2: Table S4a (Illumina read statistics)].…”
Section: Resultsmentioning
confidence: 99%
“…This is a heterogeneous gramineous plant that hybridizes interspecifically and hence has a complex genetic background. Recent molecular studies have revealed that the Miscanthus genome is unusually large (2.07–2.6 GB) [ 5 – 9 ]. In Miscanthus , inter- and intraspecific hybridization is common which is why this genus is characterized by rich genetic diversity and heterosis [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular studies have revealed that the Miscanthus genome is unusually large (2.07–2.6 GB) [ 5 – 9 ]. In Miscanthus , inter- and intraspecific hybridization is common which is why this genus is characterized by rich genetic diversity and heterosis [ 6 , 9 ]. The genetic diversity has been exploited to develop Miscanthus hybrids, which can deliver higher biomass yields and exhibit better adaptability to diverse climatic conditions than their parent species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation